Citizens’ Campaigns for Environmental Water Monitoring: Lessons From Field Experiments - Thaine H. Assumpcao; Andreja Jonoski; Iouliani Theona; Chrysovalantis Tsiakos; Maria Krommyda; Stefano Tamascelli; Andreas Kallioras; Marian Mierla; Harris V. Georgiou; Maria Miska; Christos Pouliaris; Cristian Trifanov; et al. (IEEE Access, 2019)
Advanced sensing technologies, combined with wireless sensor networks, have already demonstrated their value in monitoring urban water systems, where management is rather centralized within water utility organizations. Environmental water resources, characterized by more diverse stakeholders and overlapping management responsibilities of different agencies, present more challenging contexts for implementing novel sensing technologies. Crowdsourcing by citizens has been proposed as an alternative approach for adaptive data collection that can augment the amount of data collected, as well as bring together the diverse stakeholders and citizens in more participatory water resources management processes. This article first introduces the challenges of designing citizens' campaigns for collecting data on environmental waters. A set of developed mobile phone and web applications is then introduced, integrated within a specific platform, as it was used in the execution of citizens' campaigns for data needed in flood analysis and management. Experiences and lessons learned are presented from the field execution of citizens' campaigns in two pilot areas located in Europe - the Danube Delta in Romania, and the Kifissos catchment in Greece. Two of the campaigns are on river data collection - water levels and water velocities, and two on collecting land use/land cover data. Surveys carried out with campaign participants indicate their appreciation of the initiative, but challenges remain regarding user-friendliness of the applications. Logistic issues such as timing, duration, and pathways for data collection impacted the motivation of participants. Overall, a unique and large dataset was obtained in terms of quantitative water measurements, despite data losses due to low raw data quality. Further work lies in evaluating the usability of this dataset for local authorities.